A case study: Application of energy and exergy analysis for enhancing the process efficiency of a three stage propane pre-cooling cycle of the cascade LNG process - Najibullah Khan, N.; Barifcani, Ahmed; Tade, Moses; Pareek, V. (2016)
The propane pre-cooling cycle has been widely used in most LNG plants as the first cooling cycle in the natural gas liquefaction process. As LNG plants consume high amounts of energy, enhancements in the process design and plant operation will minimize the overall energy consumption of the plant. The aim of this study is to enhance the process efficiency of a three stage propane pre-cooling cycle of the Cascade LNG process for the large-scale LNG train by determining the optimal operating conditions of the propane evaporator that will minimize the overall energy consumption. Energy and exergy analysis methods are adopted to evaluate the process efficiency of the propane pre-cooling cycle. Six case studies were presented to determine the optimal operating conditions of the propane evaporator that gives maximum energy reduction. The propane pre-cooling cycle is modelled and simulated using Aspen HYSYS with detailed thermodynamic information obtained to calculate the exergy loss. The results of the energy and exergy analysis indicate that Case 6 gives the highest coefficient of performance (COP) and the maximum exergy efficiency compared to the baseline case, which are 15.51% and 18.76% respectively. The results indicate that by reducing the cooling duty at the intermediate stages of propane evaporator about 13.5% energy saving can be achieved compared to the baseline case.